Development of a Subsystem for Supporting a Complex of Diagnostic Procedures for the Information-Analytical System TISP - Oleksandr Palagin (V.M. Glushkov Institute of Cybernetics, 2021)
Introduction. During the implementation of the project "Transdisciplinary Intelligent Information-Analytical System for Supporting Rehabilitation Processes in a Pandemic (TISP)", all the capabilities of the basic cognitive information technology were focused on the implementation of the strategy of rehabilitation measures, which consists in taking into account the pathogenetic features of the development of the disease. In the subsystem of information and analytical support of the complex of diagnostic procedures, the central is the assessment of the effectiveness of rehabilitation based on the indicators of the electrocardiogram (ECG) and heart rate variability (HRV), control of the patient's condition using psychophysiological (PF) and psychological testing, the use of biological feedback (BF) to improve the efficiency of rehabilitation, as well as the use of PF testing for the implementation of BF. The purpose of the article is detailing the composition and functionality of a complex of diagnostic procedures for supporting rehabilitation processes in a pandemic. Results. The composition and functionality of the complex of diagnostic procedures are presented. It includes three components: first, an innovative technique for scaling electrocardiograms and heart rate variability (Universal Scoring System) with software and a miniature electrocardiograph (with the ability to use on-line mode). Secondly, the study of psychophysiological testing tools based on the software-hardware complex "Psykholot-1" with the prospect of its addition by means of Biological Feedback (BF). Thirdly, the analysis of existing means of BF therapy and their application for rehabilitation with the proposed method of rehabilitation based on BF using artificial intelligence tools that are being developed within the framework of this project. In the future, it is planned to monitor patients undergoing rehabilitation in order to develop new rules specially adapted for assessing and monitoring the current state of patients undergoing rehabilitation, as well as the effectiveness of BF for rehabilitation. To implement the BF, the Psykholot-1 complex should be used in a trainer mode with a visual presentation of PF tests to the patient in real time. Conclusions. Hardware and software systems of biomanagement must be present at every workplace of a doctor, psychologist, coach, teacher. They can not only help in the treatment of patients, but also can change motivation, mobilize personal resources, and this is what many of us lack today.